2007
DOI: 10.1042/cs20060342
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II signal transduction through the AT1 receptor: novel insights into mechanisms and pathophysiology

Abstract: The intracellular signal transduction of AngII (angiotensin II) has been implicated in cardiovascular diseases, such as hypertension, atherosclerosis and restenosis after injury. AT(1) receptor (AngII type-1 receptor), a G-protein-coupled receptor, mediates most of the physiological and pathophysiological actions of AngII, and this receptor is predominantly expressed in cardiovascular cells, such as VSMCs (vascular smooth muscle cells). AngII activates various signalling molecules, including G-protein-derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
290
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(302 citation statements)
references
References 124 publications
(148 reference statements)
7
290
0
5
Order By: Relevance
“…These data demonstrate that AngII can increase nuclear PPAR␦:Bcl-6 binding, limiting the amount of free Bcl-6 to repress the expression of inflammatory genes normally suppressed by Bcl-6. Valsartan pretreatment greatly attenuated PPAR␦:Bcl-6 binding, indicating that this effect of AngII is mediated by the angiotensin type 1 (AT-1) receptor, which mediates most of the proinflammatory actions of AngII (27). Consistent with the change in free Bcl-6, AngIIstimulated MCP-1 expression, which is known to be regulated by Bcl-6 (28), was attenuated by GW0742 (Fig.…”
Section: Ppar␦ Activation Attenuates Angii Suppression Of the Antiinfsupporting
confidence: 63%
See 1 more Smart Citation
“…These data demonstrate that AngII can increase nuclear PPAR␦:Bcl-6 binding, limiting the amount of free Bcl-6 to repress the expression of inflammatory genes normally suppressed by Bcl-6. Valsartan pretreatment greatly attenuated PPAR␦:Bcl-6 binding, indicating that this effect of AngII is mediated by the angiotensin type 1 (AT-1) receptor, which mediates most of the proinflammatory actions of AngII (27). Consistent with the change in free Bcl-6, AngIIstimulated MCP-1 expression, which is known to be regulated by Bcl-6 (28), was attenuated by GW0742 (Fig.…”
Section: Ppar␦ Activation Attenuates Angii Suppression Of the Antiinfsupporting
confidence: 63%
“…Because AngII is known to activate MAP kinase intracellular signaling pathways to promote vascular inflammation and macrophage recruitment (27,29), we examined whether PPAR␦ activation alters AngII-mediated activation of MAP kinase pathways in macrophages. We found that in mouse peritoneal macrophages AngII treatment stimulated a 2-fold increase in the phosphorylation of both the p38 and ERK1/2 MAP kinases (Fig.…”
Section: Ppar␦ Ligand Inhibits Angii-induced Activation Of Map Kinasesmentioning
confidence: 99%
“…In contrast, the selective blockade of AT1 significantly decreased the reperfusion-induced cellular calcium increase. AT1 is more abundantly expressed in the kidney endothelial cells 32 ; thus, the simultaneous blockade of these receptors may also affect PT calcium changes.…”
Section: Discussionmentioning
confidence: 99%
“…122 Moreover, Ang-II-mediated changes in the production of MMP-2 and TIMP-2 occur through AT1Rs and a TGF␤1-dependent mechanism, and not through hemodynamic effects. 96,97 …”
Section: Ang II and Other Profibrotic Factorsmentioning
confidence: 99%